2019
DOI: 10.1111/jgh.14740
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in fat de novo synthesis and chemokine ligand expression in non‐alcoholic fatty liver disease caused by inhibition of mixed lineage kinase domain‐like pseudokinase

Abstract: Background and AimReceptor‐interacting serine/threonine kinase 3 and mixed lineage kinase domain‐like pseudokinase (MLKL) have gained attention as apoptosis alternate cell death signaling molecules. We aimed to evaluate the role of MLKL in non‐alcoholic fatty liver disease (NAFLD).MethodsHepatic tissue MLKL expression was compared between NAFLD patients and healthy controls. High‐fat diet was fed to wild‐type and MLKL‐knockout (KO) mice for 12 weeks. Brown adipose fat tissue was measured by [18F]‐fluorodeoxygl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 28 publications
0
32
5
2
Order By: Relevance
“…After 18 hours of a choline-deficient methioninesupplemented diet [55] or 8 weeks of a Western diet [17], Mlkl −/− mice are indistinguishable from wild-type controls. Following 12 weeks of a high fat diet (HFD) [56], however, Mlkl −/− mice appear resistant to steatohepatitis given that MLKL-deficiency promotes reduced de novo fat synthesis and chemokine ligand expression [56]. A similar effect is seen following 12 weeks of a high fat, fructose, and cholesterol diet, where Mlkl −/− mice are markedly protected against liver injury, hepatic inflammation and apoptosis attributed to inhibition of hepatic autophagy [57].…”
Section: Metabolic Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…After 18 hours of a choline-deficient methioninesupplemented diet [55] or 8 weeks of a Western diet [17], Mlkl −/− mice are indistinguishable from wild-type controls. Following 12 weeks of a high fat diet (HFD) [56], however, Mlkl −/− mice appear resistant to steatohepatitis given that MLKL-deficiency promotes reduced de novo fat synthesis and chemokine ligand expression [56]. A similar effect is seen following 12 weeks of a high fat, fructose, and cholesterol diet, where Mlkl −/− mice are markedly protected against liver injury, hepatic inflammation and apoptosis attributed to inhibition of hepatic autophagy [57].…”
Section: Metabolic Diseasementioning
confidence: 99%
“…MLKL deficiency provides variable protection against the metabolic syndrome, depending on the challenge. MLKL deficiency appears to protect against dyslipidaemia with reduced serum triglyceride and cholesterol levels following a high fat diet [56] and Western diet [60], respectively. Whilst Mlkl −/− mice appear to have significantly improved fasting blood glucose levels given improved insulin sensitivity following 16 weeks of a high fat diet [59], there is conflicting evidence on the effect at steady state [56,59].…”
Section: Metabolic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, it was found that neither MLKL nor RIPK1 inhibition reduced inflammation [ 68 ]. Saeed et al found that patients with MAFLD exhibited increased MLKL levels compared to the non-MAFLD group and that MLKL −/− mice induced with a high-fat diet showed decreased transferase levels, triglycerides, MAFLD activity scores, steatosis score, inflammation, balloon degeneration, and expression of de novo lipogenesis (DNL) genes in the liver [ 69 ]. However, Suda found that RIPK1 antisense knockdown caused α-galactosylceramide-treated C57BL/6 mice to undergo large-scale apoptosis-type immune liver injury.…”
Section: Ripk1 and Mlkl In Mafldmentioning
confidence: 99%
“…Immunohistochemical staining for RIPK3 (Abcam, #ab194699) and MLKL (Abcam, #ab194699) were performed in these 23 liver tissues, according to the experiment protocol as previously described (Lai et al, 2015). Both RIPK3 and MLKL antibodies used for immunohistochemical staining in our study were carefully selected based on applicability, specificity, and also upon validation from other investigators (Mizumura et al, 2014;Wang et al, 2016;Saeed et al, 2019;Xu et al, 2019). A negative control was coupled with the test in which the antibody was substituted by the primary rabbit negative control.…”
Section: Immunohistochemistry and Quantificationmentioning
confidence: 99%